Dampak Pendidikan Dalam Bingkai Moderasi Beragama Ditinjau Dari Perspektif Agama Kristen - Laoli, Antonius; Tapilaha, Sandra Rosiana; Marbun, Tresa (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This research aims to explore and understand the role of education in restoring meaning in the frame of religious moderation with a focus on promoting inclusiveness, tolerance and interfaith harmony. Collaboration between teachers, families, and religious leaders in creating open discussion spaces, collaborative activities, and providing examples of religious moderation has a positive impact in shaping inclusive and tolerant attitudes towards religious differences. The research method used is a literature study by collecting and analyzing relevant sources in the fields of religious education, religious moderation, and efforts to involve families and communities. Based on the literature review, this study concludes that religious education has an important role in shaping an inclusive and tolerant attitude towards religious differences in a multicultural society. To achieve this goal, religious education needs to adopt a religious moderation approach that encourages students to understand the complexity of religion, develop critical understanding and treat religious differences as a source of wealth. In addition, this study found that involving families and communities in religious education also plays an important role in restoring the meaning of education in the frame of religious moderation.